X-ray morphology of cluster-mass haloes in self-interacting dark matter. Issue 1 (29th August 2022) - Shen, Xuejian; Brinckmann, Thejs; Rapetti, David; Vogelsberger, Mark; Mantz, Adam; Zavala, Jesús; Allen, Steven W
ABSTRACT: We perform cosmological zoom-in simulations of 19 relaxed cluster-mass haloes with the inclusion of adiabatic gas in the cold dark matter (CDM) and self-interacting dark matter (SIDM) models. These clusters are selected as dynamically relaxed clusters from a parent simulation with M_200 (1\!-\!3)× 10^15 M_ . Both the dark matter and the intracluster gas distributions in SIDM appear more spherical than their CDM counterparts. Mock X-ray images are generated based on the simulations and are compared to the real X-ray images of 84 relaxed clusters selected from the Chandra and ROSAT archives. We perform ellipse fitting for the isophotes of mock and real X-ray images and obtain the ellipticities at cluster-centric radii of r0.1\!-\!0.2R_200 . The X-ray isophotes in SIDM models with increasing cross-sections are rounder than their CDM counterparts, which manifests as a systematic shift in the distribution function of ellipticities. Unexpectedly, the X-ray morphology of the observed non-cool-core clusters agrees better with SIDM models with cross-section (σ /m)= 0.5\!-\!1 cm^2 g^-1 than CDM and SIDM with (σ /m)=0.1 cm^2 g^-1 . Our statistical analysis indicates that the latter two models are disfavoured at the 68 per cent confidence level (as conservative estimates). This conclusion is not altered by shifting the radial range of measurements or applying a temperature selection criterion. However, the primary uncertainty originates from the lack of baryonic physics in the adiabatic model, such as cooling, star formation and feedback effects, which still have the potential to reconcile CDM simulations with observations.